Torsional Behavior of High Strength Concrete Members Strengthened by Mixed Steel Fibers - Jawad Kadhim Mures; Mazin Abdul Imam Ahmed; Aqeel Hatem Chkheiwer (Journal of Engineering)
Twelve mixing steel fibers-reinforced high strength concrete beams were experimentally tested under pure torsion to investigating the concrete member torsional behavior. The first cracking torque, ultimate torsional resistance, crack patterns, effect of steel fiber ratio, effects of shape and size of hollow cross-section, and effect of stirrups reinforcement were discussed. The ratio of mixing steel fiber, different shape and size of hollow cross-section, and ratio of stirrups reinforcement were considers as major parameters. The results are shown that the width of cracks decreases and the cracks number increases with mixing steel fibers ratio increased. The first cracking torque and ultimate torsion load increased with decrease in the hollow cross-section area of high strength concrete members strengthened by steel fibers.